Modelling and simulation of matrix converter for DC chopper implementation / Rahimah Uzir - Uzir, Rahimah (2003)
The matrix converter is an advanced circuit topology capable of converting ac to ac, ac to dc, and dc to ac and dc-to-dc. Matrix converters offer many advantages over traditional topologies, such as the ability to regenerate energy back to the utility. The size of the converters can also be reduced since there are no large reactive components for energy storage . In matrix converters the switching algorithm need to be carefully calculated to ensure that the switches do not short circuit the voltages sources, and do not open circuit the current sources, thus the continuous current at the output terminal are needed. It also follows; if the number of the input-phases are equal to or less than the number of output phases, then the continuous current must available at the input terminal the advantages of this approach, it can be developed to any kind of matrix converters.